Numerical appromixation of the value of a stochastic differential game with asymmetric information - Lubomir Banas; Giorgio Ferrari; Tsiry A. Randrianasolo (Bielefeld University, Center for Mathematical Economics (IMW), 2019)
We consider a convexity constrained Hamilton-Jacobi-Bellman-type obstacle problem for the value function of a zero-sum differential game with asymmetric information. We propose a convexity-preserving probabilistic numerical scheme for the approximation of the value function which is discrete w.r.t. the time and convexity variables, and show that the scheme converges to the unique viscosity solution of the considered problem. Furthermore, we generalize the semi-discrete scheme to obtain an implementable fully discrete numerical approximation of the value function and present numerical experiments to demonstrate the properties of the proposed numerical scheme.
urn:nbn:de:0070-pub-29399744
Keywords: 330; Spieltheorie; Stochastisches Spiel; Asymmetrische Information